Pengaruh Besar Upah dan Lingkungan Kerja terhadap Kualitas Kinerja Karyawan Bank Syariah: Studi Pada Bank Syariah Kota Metro Lampung - Setia Budi, Akbar; Ambar Wati, Diana (Budgeting: Jurnal Akuntansi Syariah, 2025)
This study aims to analyze the influence of wages and work environment on the quality of employee performance in Islamic banks in Metro City, Lampung by using a quantitative approach and using multiple linear regression methods. A total of 30 respondents were selected through purposive sampling techniques. Hypothesis testing was carried out with t-test and F-test and calculation of the coefficient of determination (R²). The results of this study show that the work environment has a positive and significant influence on employee performance, while the amount of wages does not have a significant effect. This means that the improvement of employee performance is more determined by the conditions of a comfortable work environment, good social relationships, and adequate support of work facilities compared to the amount of wages received. Simultaneously, the amount of wages and the work environment had a significant effect on employee performance, with the ability to explain the variation in performance of 65.6%, while the rest were influenced by other factors such as motivation, leadership, and job satisfaction. Thus, efforts to improve employee performance should be focused on creating a conducive work environment that supports productivity.